Envisioning Green Library Initiatives: A Key Concern for 21st Century Librarians - Ogunbodede, Kolawole Francis; Omehia, Anthonia; Omehia, Anthonia (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2024)
The Green Library Initiative (GLI) is a global movement advocating for the integration of sustainable practices into library operations. Libraries, as essential repositories of knowledge and information, have a notable environmental footprint. Nigeria, a rapidly developing nation facing significant environmental challenges, stands to benefit from implementing the GLI. This paper discusses the concept of the GLI, examples of green practices suitable for Nigerian libraries, benefits of the initiative, associated challenges, and proposed solutions. It also explores the implications of the GLI for 21st-century librarians, emphasizing the pivotal role they play in driving sustainable practices and environmental education. The study underscores the need for collective efforts, policy support, and a paradigm shift towards sustainability for a greener and more sustainable future in Nigerian libraries.